Improving the level of training of IT-specialists based on analysis of labor market requirements - A. V. Gavrilov; S. V. Kulikova; G. E. Golkina (Открытое образование (Москва))
Purpose of the study. The aim of the research is to develop new approaches of improvement the level of training of IT-specialists with knowledge and skills that are in demand on the labor market. The proposed methodology for determining the competencies of IT specialists most in demand by employers includes determining the structure of demand for the competencies of IT specialists in Russia in the digital economy using the developed application. The application of the methodology for the analysis of the content of the academic discipline will make it possible to formulate recommendations on the selection of software tools and technologies used to teach students practical skills in this discipline based on the current requirements of the labor market.Materials and methods. The main idea of the research is to develop a universal methodology that allows you to coordinate the content of the theoretical and practical components of academic disciplines with dynamically changing qualification requirements for specialists in the IT industry from employers. The study of existing approaches to determining the qualification requirements for IT industry specialists has shown that the most effective methodology can be based on the analysis of large volumes of statistical data, the use of modern methods of analysis Data mining, Text mining, and the use of databases to store the collected information. The article discusses a comprehensive methodology for collecting and analyzing information collected from the websites of recruiting companies, including: 1) an algorithm for determining the competencies of IT specialists most in demand by employers; 2) a database model for storing information about vacancies; 3) an algorithm for bringing unstructured textual information about a vacancy to a factual database; 4) authoring analytical application based on the Qlik Sence BI system, which allows monitoring vacancies. The novelty of the proposed approaches lies in the possibility of operational updating of the content of academic disciplines based on labor market requirements.It is proposed to define the indicator of the demand for professional competence (demand for specialists who own IT technology) as the ratio of the number of vacancies in which this competency is mentioned to the total number of vacancies in potential areas of graduate work. It is obvious that those competencies that will show the best results and are in demand on the labor market.Based on an analysis of the requirements of employers for applicants posted on the website of the Russian company HeadHunter, an example of determining the current competencies in the field of database technologies is considered. An analytical application developed on the basis of the Qlik Sence BI system was used as a tool. Information was collected using the Datacol parser (module “parser resume hh.ru”).Results. In general, the proposed methodology can be used to analyze the relevance of software tools used to teach students practical skills within the academic discipline. The specific results obtained as a result of the study can be useful in the formation of a workshop for teachers of such disciplines as “Databases”, “Database Management Systems” and other disciplines in this area.Conclusion. In the conditions of the dynamic development of the sphere of information technology, constant updating of the disciplines of this profile is a prerequisite for the quality training of IT specialists. The article proposes a methodology for choosing software products used for teaching students based on current labor market requirements. The article is based on the results of scientific and practical development “Development of new approaches to the preparation of ITspecialists in the Plekhanov Russian University of Economics, taking into account the requirements of employers”, carried out as part of an internal Plekhanov Russian University of Economics grant. According to the results of scientific and practical development, a certificate of registration of a computer program was received.